PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBANTUAN MEDIA WORDWALL TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN TEKS NONFIKSI SISWA SEKOLAH DASAR - Pani Herlina , Hafiziani Eka Putri, Nadia Tiara Antik Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The study was conducted to see the importance of reading comprehension of non- fiction texts that must be mastered by elementary school students. However, stu- dents' mastery of this ability is low. One of the causes of the low level is that the learning model used by teachers in the classroom has not emphasized student activ-ity in learning. The purpose of this study was to determine the influence and im-provement through different actions and groups using four indicators of reading comprehension ability for fifth grade elementary school students on historical non- fiction text material. The experimental group used the Jigsaw cooperative learning model assisted by wordwall media, the control group used the STAD cooperative learning model. The research method used was a quasi-experimental with a non- equivalent control group design and a sample size of 60 people using the purposive sampling technique. This study collected two data to be analyzed, namely test data in the form of pre-test and post-test, while non-test data were in the form of obser- vation and documentation. The results of the study showed that the increase in stu- dents' reading comprehension ability of non-fiction texts using the Jigsaw coopera- tive learning model assisted by wordwall media was better than students who used the STAD cooperative learning model and there was a positive influence in using the Jigsaw cooperative learning model assisted by wordwall media on students' reading comprehension of non-fiction texts. Thus, the Jigsaw cooperative learning model assisted by wordwall media can be an alternative that can be used in learn- ing, especially in class V for historical non-fiction text material.